A comparative study of school environment for students' skills development in Malaysia and Indonesia - Sobri, Kiagus Muhammad; Hanum, Farida; Zulnaidi, Hutkemri; Ahmad, Abdul Razaq; Alfitri, - (Elsevier, 2017)
The cultural support and school environment for students’ skills development in Malaysia and Indonesia were examined. School environment in this study consisted of cultural support and classroom activities in both countries. Students’ skills in this research referred to soft skills gained from daily experiences in schools. The focus of this paper was to evaluate the levels of school environments and students’ skills as well as the differences in variables in both countries. In total, 400 Indonesian students and 528 Malaysian students were involved in this study. The instrument used was validated via a pilot study where the Cronbach alpha values showed that all items had high reliability and could be used in the actual study. Data collected were analyzed focusing on descriptive and inferential statis- tics. The results showed that overall, the school environments and student’s skills were at the moderate level. This means that the school environment in both countries requires strategic actions for promoting a high level of soft skills. The inferential statistics demonstrated that students in Malaysia seemed to have better support compared to Indonesian students. However, the results indicated that Indonesian students have better soft skills than Malaysian students, especially in leadership communication and cooper- ation. Students from both countries had similar levels of thinking, interpersonal, man- agement, and ICT skills. The SEM data showed that students in Malaysia were more likely to have better soft skills as they have been positively supported by school and classroom activities. The data showed that classroom activities had a direct impact on soft skills development among Indonesian students. Based on these? ndings, speci? c planning is urgently needed to provide holistic support to improve school environments as a way to promote students’ skills. © 2017 Kasetsart University.